2019
DOI: 10.3168/jds.2018-15847
|View full text |Cite
|
Sign up to set email alerts
|

Effect of energy source in calf milk replacer on performance, digestibility, and gut permeability in rearing calves

Abstract: Current calf milk replacer (CMR) compositions significantly differ from whole milk in their levels of energy, protein, and minerals. Energy source is one of the major differences, as CMR contains high levels of lactose, whereas whole milk contains higher levels of fat. The aim of this study was to determine the effect of partially exchanging lactose for fat on performance, digestibility, and gut permeability in calves fed twice daily on a high feeding plane. Lactose and fat were exchanged in the CMR formulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 32 publications
1
35
0
4
Order By: Relevance
“…With exchanging lactose for fat, CMR osmolality is reduced and would reduce gut permeability . To the contrary, however, Amado et al (2019) showed a higher gut permeability with HF CMR. The current experiment indicated a reduced occurrence of healthrelated events with HF CMR, although these events were mainly respiratory and not digestive.…”
Section: Health Observationsmentioning
confidence: 71%
See 2 more Smart Citations
“…With exchanging lactose for fat, CMR osmolality is reduced and would reduce gut permeability . To the contrary, however, Amado et al (2019) showed a higher gut permeability with HF CMR. The current experiment indicated a reduced occurrence of healthrelated events with HF CMR, although these events were mainly respiratory and not digestive.…”
Section: Health Observationsmentioning
confidence: 71%
“…Animals that have low phosphate at birth (<2.26 mmol/L) have been shown to have greater risk for diarrhea, with scouring calves having lower phosphate status than healthy calves up to 20 d of age (Jagoš et al, 1981, citing Cabello et al, 1977. Amado et al (2019) found higher fecal consistency (i.e., less thin) in the first week after birth when feeding high fat.…”
Section: Blood Traitsmentioning
confidence: 87%
See 1 more Smart Citation
“…These authors argued that this hypertonic milk replacer which caused intestinal osmotic pressure was greater than plasma osmolality and that this could exert an osmotic pressure on cell lining and on the tight junctions. Amado et al [ 93 ] studied feeding in male calves high-fat milk replacers, and observed an increased intestinal permeability compared with lactose-rich milk replacers. Curiously, Urie et al [ 94 ] observed a significant association between the amount of fat per day in liquid and increased calves’ mortality; so, the effect of fat content, fat type in the milk replacer and the total amount of fat consumed on gut permeability should be further studied.…”
Section: Considerations To Advance In Future Nutritional Strategiementioning
confidence: 99%
“…Pisoni and Relling [ 95 ] hypothesized that supplementation with a prebiotic (yeast fermentation products) could stimulate the secretion of the gut hormone glucagon-like peptide 2 (GLP-2) by inducing changes in gut microbiota. GLP-2 is associated with intestinal permeability regulation and could enhance the mitogenic action of IGF-1 to synergistically benefit GIT development [ 93 ]. However, these authors [ 95 ] did not observe benefits of prebiotic supplementation on performance parameters, plasma GLP-2 concentration, intestinal permeability when supplementing these yeast fermentation products in the milk and starter in heifers.…”
Section: Considerations To Advance In Future Nutritional Strategiementioning
confidence: 99%